Simultaneous determination of tobacco minor alkaloids and tobacco‐specific nitrosamines in mainstream smoke by dispersive solid‐phase extraction coupled with ultra‐performance liquid chromatography/tandem orbitrap mass spectrometry. (6th September 2018) - Zhang, Xiaotao; Wang, Ruoning; Zhang, Li; Ruan, Yibin; Wang, Weiwei; Ji, Houwei; Lin, Fucheng; Liu, Jian
Abstract : Rationale: The minor alkaloids in tobacco play an important role in the chemical composition of cigarette smoke, and they are precursors of tobacco‐specific nitrosamines (4‐(methylnitrosamino)‐1‐(3‐pyridyl)‐1‐butanone (NNK), N ‐nitrosonornicotine (NNN), N ‐nitrosoanabasine (NAB) and N ‐nitrosoanatabine (NAT)). NNN and NNK are classified as group 1 carcinogens. A method quantitating both tobacco minor alkaloids and tobacco‐specific nitrosamines in mainstream smoke has not been reported. Methods: Tobacco minor alkaloids and tobacco‐specific nitrosamines in cigarette mainstream smoke were extracted by sonication. The extract was cleaned up by dispersive solid‐phase extraction, and separation was achieved via ultra‐performance liquid chromatography/tandem orbitrap mass spectrometry. Results: The method was validated by analysis of six replicate samples spiked with three levels of the analyses. The mean recoveries for the six replicates were from 84.7% to 118% with less than 15% relative standard deviation except myosmine at the low spiked level and the calculated detection limits were 0.066 to 13.2 ng/cig, respectively. The mean concentrations of nicotyrine, anabasine, nornicotine, anatabine, myosmine, 2, 3‐bipyridine, cotinine, nicotelline, N ‐formylnornicotine, NNK, NNN, NAB and NAT in 30 different brands of commercial cigarette smoke under the ISO smoking regimen were 2.50 μg/cig, 2.34 μg/cig, 3.21 μg/cig, 5.78 μg/cig, 2.83 μg/cig, 1.05 μg/cig, 1.55 μg/cig, 0.55 μg/cig, 2.48 μg/cig, 6.06 ng/cig, 3.62 ng/cig, 0.40 ng/cig and 6.15 ng/cig, respectively. Conclusions: The proposed method was suitable for analysis of tobacco minor alkaloids and tobacco‐specific nitrosamines in cigarette mainstream smoke.